1999
DOI: 10.1016/s0304-4165(98)00122-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of peroxide in AC electrical field exposure effects on Friend murine erythroleukemia cells during dielectrophoretic manipulations

Abstract: The effects of AC field exposure on the viability and proliferation of mammalian cells under conditions appropriate for their dielectrophoretic manipulation and sorting were investigated using DS19 murine erythroleukemia cells as a model system. The frequency range 100 Hz-10 MHz and medium conductivities of 10 mS/m, 30 mS/m and 56 mS/m were studied for fields generated by applying signals of up to 7V peak to peak (p-p) to a parallel electrode array having equal electrode widths and gaps of 100 μm. Between 1 kH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 56 publications
4
59
0
Order By: Relevance
“…Buffer additives such as BSA, pluronic F-68, anti-oxidant compound, and catalase are known to provide either cell membrane stability, reduction of oxidative stress, or decreased aggregation. 48,49 BSA has been known to reduce the non-specific cell surface interactions and is widely used in flow cytometry and microfluidic applications. 49 Pluronic F-68 is a stabilizer of cell membranes; it reduces potential for membrane shearing by enhancing mechanical strength of the cell membrane with short-term exposure.…”
Section: Buffer Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Buffer additives such as BSA, pluronic F-68, anti-oxidant compound, and catalase are known to provide either cell membrane stability, reduction of oxidative stress, or decreased aggregation. 48,49 BSA has been known to reduce the non-specific cell surface interactions and is widely used in flow cytometry and microfluidic applications. 49 Pluronic F-68 is a stabilizer of cell membranes; it reduces potential for membrane shearing by enhancing mechanical strength of the cell membrane with short-term exposure.…”
Section: Buffer Optimizationmentioning
confidence: 99%
“…50 It has been shown that hydrogen peroxide is produced when sugar-containing buffer is exposed to AC electric fields; the addition of catalase to buffer allows hydrogen peroxide decomposition and reduces potential for cell damage. 48 These additives were used in the sample buffer to improve the device performance based on their known beneficial effects on cells and ability to increase recovery by lowering nonspecific adhesion between cell to cell and cell to contact surfaces. …”
Section: Buffer Optimizationmentioning
confidence: 99%
“…DEP is a technique whereby the frequency-dependent behaviour of cells is determined in nonuniform electric fields, and from this information regarding the electrical properties of the cell can be inferred [8; 9; 10]. DEP and related techniques have been used to characterise a wide range of cellular processes in terms of these biophysical properties in cancer research [11][12][13][14][15][16][17][18]. Our studies have also incorporated a flow cytometric technique to measure membrane potential as an additional biophysical parameter to be considered in our assessment of the cell line panel.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations in our lab and others have established that exposure to electric fields from DEP electrodes akin to those used in these experiments does not alter cell viability. [43][44][45] In our initial adipose-derived SVF fractionation experiments, eluted cell fractions were collected into tissue culture media, cultured for 12−24 h and assayed for plastic adherence. Cultures of viable cells possessing a fibroblast-like morphology typically associated with adipose-derived mesenchymal stem cell cultures were observed, confirming that cells remain viable following fractionation by DEP-FFF.…”
Section: Resultsmentioning
confidence: 99%